Connecting urban form and travel behaviour towards sustainable development in Kaduna, Nigeria - Yakubu Aliyu Bununu, 1974-, author 603961 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Doktor Falsafah (Perancangan Bandar dan Wilayah))